From passive to engaged learnng: an ICAP intervention in an ESL classroom - Kapong, Joyce Morris (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
Past studies claimed that sociocultural factors are among the causes of disengagement from intellectual tasks among students in an ESL classroom. The disengagement resulted in low English language proficiency level. This paper describes the process of designing and developing an English language instruction based on the ICAP learning framework by Chi and Wylie (2014). The instruction functioned as an intervention to engage 45 pre-university ESL learners at a Malaysian public university to improve their English proficiency level. Data were collected and analysed through design-based research methods. The intervention, which was designed based on ICAP and culturally responsive teaching (CRT) developed by Geneva Gay (2010), uncovered three main characteristics – achieving high English proficiency level is regarded as a primary goal, the collaboration among learners during intellectual tasks develops both the collective and the individual student, and a respectful, inclusive and fun teaching approach is a major component in the cognitive and affective processes of learning. The intervention also resulted in evident transformative effects within the learners such as being able to attain autonomy throughout the learning experience, to distinguish concurrent cognitive processes during intellectual tasks, and to nurture respect and inclusivity in an ESL classroom. Finally, this paper discusses the impact of relevance when constructing teaching and learning activities, the importance of designing for individual and collective development, and the construction of pragmatic interventions as solutions to problems in English learning.